Geographical Variation in Physical Fitness Among Chinese Children and Adolescents From 2005 to 2014 - Dong, Yanhui; Chen, Manman; Song, Yi; Ma, Jun; Lau, Patrick W. C. (Frontiers in Public Health, 2021)
Introduction: To examine the geographical variation in change in the levels of physical fitness from 2005 to 2014 among Chinese children. Methods: A total of 663,813 children 7 to 18 years of age with physical fitness data in 2005, 2010 and 2014, participated in the study. Physical fitness was assessed using 6 tests and scores were aggregated to form a summary physical fitness indicator (PFI). Results: Over the study period, there was an increase in the proportion of high PFI (from 15.3% in 2005 to 19.0% in 2014, Ptrend<0.05) and a decrease in the proportion of low PFI (from 30.6% to 29.8%, Ptrend<0.05). Children and adolescents in the eastern provinces of China showed a high proportion of high PFI with an increasing trend over time, while those in the western provinces had a high proportion of low PFI with a decreasing trend over time (P<0.05). Conclusions: Fitness levels among Chinese children showed an improved trend from 2005 to 2014. Region-specific interventions with priority policies can be useful to sustainably narrow geographical variation in Chinese children, especially in the western provinces.